2014
DOI: 10.1016/j.leukres.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the BCR-ABL1 kinase domain in chronic-phase chronic myelogenous leukemia treated with tyrosine kinase inhibitors in practice: Study by the Nagasaki CML Study Group

Abstract: An appropriate trigger for BCR-ABL1 mutation analysis has not yet been established in unselected cohorts of chronic-phase chronic myelogenous leukemia patients. We examined 92 patients after 12 months of tyrosine kinase inhibitor (TKI) treatment in Nagasaki Prefecture, Japan. Univariate analysis revealed that significant factors associated with not attaining a major molecular response (MMR) were the presence of the minor BCR-ABL1 fusion gene, a low daily dose of TKI, and the emergence of BCR-ABL1 kinase domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…Several reports have demonstrated that BCR-ABL Ins35bp is detected mainly in patients who have achieved hematological/cytogenetic response, but not DMR, despite long-term TKI treatment. (6,12,15,43) In contrast, extremely low amounts of BCR-ABL Ins35bp were detected in patients with newly-diagnosed, previously untreated CML (data not shown). We found that TKI treatment inhibits recruitment of RNA polymerase a toward genomic BCR-ABL, which positively regulates both transcription and pre-mRNA intron splicing, resulting in a relative increase in the amount of BCR-ABL Ins35bp with a decrease of total BCR-ABL transcript level.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Several reports have demonstrated that BCR-ABL Ins35bp is detected mainly in patients who have achieved hematological/cytogenetic response, but not DMR, despite long-term TKI treatment. (6,12,15,43) In contrast, extremely low amounts of BCR-ABL Ins35bp were detected in patients with newly-diagnosed, previously untreated CML (data not shown). We found that TKI treatment inhibits recruitment of RNA polymerase a toward genomic BCR-ABL, which positively regulates both transcription and pre-mRNA intron splicing, resulting in a relative increase in the amount of BCR-ABL Ins35bp with a decrease of total BCR-ABL transcript level.…”
Section: Discussionmentioning
confidence: 88%
“…It has remained unclear how alternatively spliced BCR‐ABL Ins35bp variants can be acquired in CML cells under TKI treatment, and why mis‐splicing reproducibly occurs at the specific sites of intronic 35 bp in ABL intron 8. Several reports have demonstrated that BCR‐ABL Ins35bp is detected mainly in patients who have achieved hematological/cytogenetic response, but not DMR, despite long‐term TKI treatment . In contrast, extremely low amounts of BCR‐ABL Ins35bp were detected in patients with newly‐diagnosed, previously untreated CML (data not shown).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Of note, Case #3 exhibited an infrequent type of mutation and responded less well to nilotinib and better to dasatinib treatment. The respective resistance patterns could have resulted from individual patient factors such as medical history, therapy adherence, amino acid substitutions, or other unidentified mechanisms but it might also result from the structural affinity of each TKI to each mutation [5]. Because of the limited number of clinical reports, it remains uncertain whether the exon 6 frameshift acts differently against dasatinib and nilotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, alternative splicing variants such as an exon 7 deletion, insertion of 35 intronic nucleotides at the junction of exon 8/9, and an exon 6 frameshift; i.e. a CAGG transnucleotide insertion at the junction of exon 5/6, have been proposed as mechanisms of TKI resistance [3,4], although the clinical significance of these mutations in the effectiveness of TKIs remains controversial [2,3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%